Design and Development of IoT Based Smart Irrigation Sensing, Control and Monitoring System for Agricultural Applications - Jain, Ravi Kant (E-business technologies conference proceedings, 2021)
In modern days, farm activities are transforming from manual and static to intelligent systems in order to enhance the productivity of agricultural crops yielding efficient resource utilization through automation. In agriculture, the most important part is the utilization of water in efficient manners through irrigation where the traditional irrigation systems don't encounter the use of excess water during irrigation. By using smart intervention through the Internet of Things (IoT), smart irrigation with sensing, control, and monitoring systems is proposed in this paper. Architecture for IoT-based irrigation systems is designed where soil moisture, temperature, and humidity level are studied. This system provides the information of soil and environmental conditions in the user mobile phone with IoT based approach. Thus, the user can monitor the field/plantation condition in real-time from any remote location.